Cytokinin Metabolism of Pathogenic Fungus Leptosphaeria maculans Involves Isopentenyltransferase, Adenosine Kinase and Cytokinin Oxidase/Dehydrogenase - Trdá, Lucie; Barešová, Monika; Šašek, Vladimír; Nováková, Miroslava; Zahajská, Lenka; Dobrev, Petre I.; Motyka, Václav; Burketová, Lenka (Frontiers in Microbiology, 2017)
Among phytohormones, cytokinins (CKs) play an important role in controlling crucial aspects of plant development. Not only plants but also diverse microorganisms are able to produce phytohormones, including CKs, though knowledge concerning their biosynthesis and metabolism is still limited. In this work we demonstrate that the fungus Leptosphaeria maculans, a hemi-biotrophic pathogen of oilseed rape (Brassica napus), causing one of the most damaging diseases of this crop, is able to modify the CK profile in infected B. napus tissues, as well as produce a wide range of CKs in vitro, with the cis-zeatin derivatives predominating. The endogenous CK spectrum of L. maculans in vitro consists mainly of free CK bases, as opposed to plants, where other CK forms are mostly more abundant. Using functional genomics, enzymatic and feeding assays with CK bases supplied to culture media, we show that L. maculans contains a functional: i) isopentenyltransferase (IPT) involved in cZ production; ii) adenosine kinase (AK) involved in phosphorylation of CK ribosides to nucleotides; and iii) CK-degradation enzyme cytokinin oxidase/dehydrogenase (CKX). Our data further indicate the presence of cis-trans isomerase, zeatin O-glucosyltransferase(s) and N6-(Δ2-isopentenyl)adenine hydroxylating enzyme. Besides, we report on a crucial role of LmAK for L. maculans fitness and virulence. Altogether, in this study we characterize in detail the CK metabolism of the filamentous fungi L. maculans and report its two novel components, the CKX and CK-related AK activities, according to our knowledge for the first time in the fungal kingdom. Based on these findings, we propose a model illustrating CK metabolism pathways in L. maculans.